Moral Education of Street Children at PPAP Seroja Surakarta - Badrus Zaman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to find out the concept of moral education given by PPAP Seroja institution to street children in Surakarta, the obstructing factors in implementing moral education to the to street children, and the level of moral development of street children after being provided with moral education by PPAP Seroja Surakarta institution. This study belongs to descriptive qualitative research. The data were collected through observation, documentation, and interview. The collected data were analyzed by using interactive analysis including three components, namely data reduction, data display, and conclusion drawing. The result shows: 1) the moral education of street children conducted by PPAP Seroja Surakarta aims to help the moral development as well as foster good moral attitudes or good character of the children. 2) the obstructing factors in implementing the moral education to the street children found in the children themselves. Most of them are not aware to the importance of moral education, lack of competence, lack of parents’ attention. 3) The level of moral development of street children after being provided with moral education at PPAP Seroja Surakarta is at the conventional level, namely at level III (orientation to the group of “good children”) and level IV (low-order orientation).